‘Read To Me’ / Nurul Nadhirah Ramli - Ramli, Nurul Nadhirah (2020)
When dealing with daily routines, some may experience difficulties in wanting to just seating down and read. They might need to be focus on reading and stop doing other works. Physical books may required all of their attentions in just reading. Thus the creation of audiobook. The “Read to Me” help to in helping people to listen to their favourite books while doing other activities. For instance, this audiobook can be play while cooking which are most suitable for those that are started to learn cooking. It will read all the steps and recipes while they are preparing and cooking. Other than that, this audiobook can also be play while exercising, driving or house cleaning. Beside that, young reader or people that are trying to learn to read will get benefit from this audiobook. It is well know that audiobook can help with learning, thus the “Read to Me” will able to assist them in learning new words and the pronunciation while seeing the whole texts in the physical book. They can see the spelling of certain words with how to properly pronounce it. Thus through the purpose of educating, this audiobook can be a big help to the community.Beside that, while hearing to others’ reading, it can also become a therapeutic session. Such as hearing a soothing voice reciting a story to the listener can let them to visualize the story and deepening the understanding even better. With this purpose, listener can enjoy themselves even better.